Agritourism: The Role of Farm-to-Table in Promoting Local Cuisine and Return Visits - Ninh Nguyen; Le Thi Tran; Anh Nu Nguyet Nguyen (Journal of Human, Earth, and Future)
This exploration probes into the captivating effect of agritourism, anchored in farm-to-table traditions, on the enrichment of local culinary adventures and the allure for patrons to return, employing Self-Determination Theory to scrutinize visitor interactions. The primary goal is to investigate the intricate dance between perceived autonomy, competence, and connectedness, and how they shape perceived authenticity and the tendency for return visits, highlighting the pivotal influence of perceived cost. Information was gathered via a survey involving 354 individuals, and the connections were explored through Partial Least Squares Structural Equation Modeling (PLS-SEM). Results reveal that the perception of competence exerts the most significant positive influence on the sense of authenticity and the likelihood of return visits. Nonetheless, the dynamic interaction between perceived financial burden and authenticity revealed a negative correlation with subsequent visits, indicating that increased expenditures may diminish the advantageous effects of genuine experiences. This research emphasizes the importance of aligning authentic experiences with economic viability in the realm of agritourism. Ventures, offering valuable perspectives for operators to elevate visitor engagement, thereby fostering satisfaction and loyalty. The implications of these findings extend into the realm of enhancing the design of agritourism experiences.